Impact of Phytase Supplementation on Meat Quality of Heat-Stressed Broilers - Clay J. Maynard; Craig W. Maynard; Garrett J. Mullenix; Alison Ramser; Elizabeth S. Greene; Mike R. Bedford; Sami Dridi (Animals, 2023)
Heat stress (HS) is one of the most challenging stressors to poultry production sustainability. The adverse effects of HS range from feed intake and growth depression to alteration of meat quality and safety. As phytase supplementation is known to improve nutrient utilization and consequently growth, we undertook the present study to evaluate the effects of dietary phytase on growth and meat quality in heat-stressed broilers. A total of 720 day-old hatch Cobb 500 chicks were assigned to 24 pens within controlled environmental chambers and fed three diets: Negative Control (NC), Positive Control (PC), and NC diet supplemented with 2000 phytase units (FTU)/kg) of quantum blue (QB). On day 29, birds were exposed to two environmental conditions: thermoneutral (TN, 25 °C) or cyclic heat stress (HS, 35 °C, 8 h/d from 9 a.m. to 5 p.m.) in a 3 × 2 factorial design. Feed intake (FI), water consumption (WI), body weight (BW), and mortality were recorded. On day 42, birds were processed, carcass parts were weighed, and meat quality was assessed. Breast tissues were collected for determining the expression of target genes by real-time quantitative PCR using the 2−ΔΔCt method. HS significantly increased core body temperature, reduced feed intake and BW, increased water intake (WI), elevated blood parameters (pH, SO2, and iCa), and decreased blood pCO2. HS reduced the incidence of woody breast (WB) and white striping (WS), significantly decreased drip loss, and increased both 4- and 24-h postmortem pH. Instrumental L* and b* values were reduced (p < 0.05) by the environmental temperature at both 4- and 24-h postmortem. QB supplementation reduced birds’ core body temperature induced by HS and improved the FCR and water conversion ratio (WCR) by 1- and 0.5-point, respectively, compared to PC under HS. QB increased blood SO2 and reduced the severity of WB and WS under TN conditions, but it increased it under an HS environment. The abovementioned effects were probably mediated through the modulation of monocarboxylate transporter 1, heat shock protein 70, mitogen-activated protein kinase, and/or glutathione peroxidase 1 gene expression, however, further mechanistic studies are warranted. In summary, QB supplementation improved growth performance and reduced muscle myopathy incidence under TN conditions. Under HS conditions, however, QB improved growth performance but increased the incidence of muscle myopathies. Therefore, further QB titration studies are needed.